Optimization Of Micro, Small and Medium Enterprise Financial Management Through Android-Based Zazan Mobile Application for Efficiency of Digital Economy Sustainability - Yoga, Titan Parama; Setiana, Elia; Hamzah, Encep; Budiman, Budiman; Sarifiyono, Aggi Panigoro (LPPM STMIK Mardira Indonesia, 2024)
In order to sustain and grow a firm, financial management is essential. This procedure is essential for obtaining profit and loss data, preventing employee and business partner fraud, and separating personal and business funds to determine the company's financial situation accurately. Informal MSME actors multitask and operate as small business owners, entrepreneurs, and managers of all business issues. So, there is not enough time to document the financials of a corporation. Making financial records requires basic knowledge, which makes the work feel challenging, intricate, and time-consuming. One way to address this issue is making the Android mobile application